Allergen profile of patients from central Kerala, India - AKHILESH KUNOOR,; HARILAKSHMANAN PERUVAMBA,; JAMES P.T,; RAKESH.P.S, (International Journal of Pharma and Bio Sciences, 2017)
Allergic disorders manifest in various forms like allergic rhinitis, asthma, skin allergy and allergic conjunctivitis. The current study was done in a tertiary care centre at Kochi with an objective to study the pattern of allergens tested positive in suspected atopic patients from central Kerala, southern India. Information was collected from health information system regarding all atopic patients in whom allergic skin prick test was done for aeroallergens and food allergens during Jan 1st 2012 to December 31st 2013. Most Common allergic disease for which testing was done was for Asthma (69.8%) followed by Allergic Rhinitis (59.7%). Housefly was the most common allergen observed 53.26% (74/139) followed by rice grain dust 47.5% (66/139). Insect allergens were more common in all conditions as compared to other allergens. Prawn was the most common food allergen identified. Regional variation exists in the pattern of allergic disease manifestation and nature of allergens.